The Role of Indonesia to Create Security and Resilience in Cyber Spaces [Peran Indonesia dalam Membentuk Keamanan dan Ketahanan di Ruang Siber] - Rai, I Nyoman Aji Suadhana; Heryadi, Dudy; Kamaluddin N., Asep (Sekretariat Jenderal DPR RI, 2022)
This article discusses Indonesia’s role in securing cyberspace or cyber resilience in the scope of domestic, bilateral and multilateral. Since the establishment of the National Cyber and Crypto Agency (BSSN) in 2017, Indonesia has reported many cases of cyber-attacks both in the government and in the private sphere. This article aims to find out what roles that Indonesia did in shaping cyber security and resilience in the sphere of the domestic, bilateral and multilateral. This article uses a descriptive method with literature review by using secondary data from a literature review that is available. The result of this article is that Indonesia acts as a Protectee, Mediator, and Balancer in accordance with the behavior that is shown in each phenomenon such as domestic, bilateral and multilateral (regional), which depend on the dynamic situation. However, it does not replace Indonesia’s position as a country with a status that is not in alliance with other countries, namely independence and active (Bebas-Aktif).AbstrakArtikel ini membahas tentang peran Indonesia di dalam mengamankan ruang siber atau cyberspace di lingkup domestik, bilateral dan multilateral. Sejak dibentuknya Badan Siber dan Sandi Negara atau BSSN pada tahun 2017, Indonesia melaporkan mendapatkan begitu banyak serangan siber baik di lingkungan pemerintahan maupun di lingkup swasta. Artikel ini bertujuan untuk mengetahui peran yang dilakukan oleh Indonesia dalam membentuk keamanan dan ketahanan siber di lingkup domestik, bilateral dan multilateral. Metode riset yang digunakan adalah metode deskriptif melalui kajian literatur dengan menggunakan data sekunder dari kajian literatur yang sudah tersedia. Hasil riset menunjukan bahwa Indonesia berperan sebagai Protected, Mediator, dan Balancer sesuai dengan perilaku yang ditunjukkan di masing – masing situasi baik domestik, bilateral maupun situasi multilateral yang cenderung dinamis, namun tidak mengganti posisi Indonesia sebagai negara dengan statusnya yang tidak beraliansi dengan negara lainnya yaitu bebas aktif.